Indirect effect of insulin to suppress endogenous glucose production is dominant, even with hyperglucagonemia. - Mittelman, S D (1997)
Suppression of endogenous glucose production (EGP) is one of insulin's primary metabolic effects and failure of this action is a major contributor to fasting hyperglycemia of type 2 diabetes mellitus. Classically, insulin was thought to suppress the liver directly, via hyperinsulinemia in the portal vein. Recently, however, we and others have demonstrated that at least part, and possibly most of insulin's action to suppress EGP is normally mediated via an extrahepatic (i.e., indirect) mechanism. We have suggested that this mechanism involves insulin suppression of adipocyte lipolysis, leading to lowered FFA and reduced EGP ("Single Gateway Hypothesis"). Previous studies of the indirect insulin effect from this laboratory were done under conditions of lowered portal glucagon. Because of the possibility that the direct (i.e., portal) effect of insulin may have been underestimated with hypoglucagonemia, these studies examined the relative importance of portal insulin, versus peripheral insulin (administered at one-half the dose to equalize peripheral insulin levels) at four rates of portal glucagon infusion: 0, 0.65 (under-), 1.5 (basal-), and 3.0 ng/kg per min (over-replacement). Portal versus peripheral insulin suppressed steady-state EGP to the same extent (52%), confirming that the primary effect of insulin to suppress EGP is via the peripheral mechanism. This conclusion was maintained regardless of portal glucagonemia, although there was some evidence for an increase in the direct insulin effect at hyperglucagonemia. The indirect effect of insulin is the primary mechanism of steady-state EGP suppression under normal conditions. The direct effect increases with hyperglucagonemia; however, the indirect effect remains predominant even under those conditions.